Epiphany - Borsch, Frederick Houk. (Minneapolis : Fortress Press, 1989)
Vol. discusses the appointed lessons for the Epiphany of Our Lord and the Sundays after the Epiphany.
Keywords: Bible -- Homiletical use; Bible -- Liturgical lessons, English; Epiphany season -- Sermons